2014
DOI: 10.1016/j.drugalcdep.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Is residential treatment effective for opioid use disorders? A longitudinal comparison of treatment outcomes among opioid dependent, opioid misusing, and non-opioid using emerging adults with substance use disorder

Abstract: Background Opioid misuse and dependence rates among emerging adults have increased substantially. While office-based opioid treatments (e.g., buprenorphine/naloxone) have shown overall efficacy, discontinuation rates among emerging adults are high. Abstinence-based residential treatment may serve as a viable alternative, but has seldom been investigated in this age group. Methods Emerging adults attending 12-step-oriented residential treatment (N=292; 18–24yrs, 74% Male, 95% White) were classified into opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…One retrospective study found that emerging adults (aged 18 to 25) were significantly less likely to be retained in an office-based buprenorphine program than older adults (17% versus 45% at 12 months, respectively) (Schuman-Olivier, Weiss, Hoeppner, Borodovsky, & Albanese, 2014). Further research is needed to compare and combine abstinence-based residential treatment with outpatient care (including office-based buprenorphine therapy) for opioid-using young adults (Schuman-Olivier, Claire Greene, Bergman, & Kelly, 2014). …”
Section: Obstacles To Effective Harm Reduction For Young Adult Empo Umentioning
confidence: 99%
“…One retrospective study found that emerging adults (aged 18 to 25) were significantly less likely to be retained in an office-based buprenorphine program than older adults (17% versus 45% at 12 months, respectively) (Schuman-Olivier, Weiss, Hoeppner, Borodovsky, & Albanese, 2014). Further research is needed to compare and combine abstinence-based residential treatment with outpatient care (including office-based buprenorphine therapy) for opioid-using young adults (Schuman-Olivier, Claire Greene, Bergman, & Kelly, 2014). …”
Section: Obstacles To Effective Harm Reduction For Young Adult Empo Umentioning
confidence: 99%
“…Medication for opioid use disorders (MOUD), in the form of opioid agonist or antagonist medication, is the only evidence-based treatment for youth OUD ( Committee on Substance Use and Prevention, 2016 ). Unfortunately, it has proven enormously difficult to engage youth in OUD treatment ( Hadland et al, 2017 ), and they drop out of care at alarmingly high rates (e.g., Schuman-Olivier et al, 2014 ). To address this challenge we propose a conceptual framework to organize efforts to engage and retain youth and families across the continuum of MOUD services.…”
Section: Family-based Tele-interventions For Youth Moud: Framework Anmentioning
confidence: 99%
“…For example, Matson et al 2014 reported rates of illicit opioid abstinence of up to 85% for those youth who are able to remain in treatment and continue to receive buprenorphine (Matson et al, 2014). Conversely, observational data on young adults with OUD who received a short (3-day) buprenorphine detoxification in an outpatient setting, indicate lower rates of abstinence (12% abstinent at six months)(Gandhi et al, 2003) although these rates are higher when detoxification is implemented in residential treatment settings (approximately 31-43% at six months) (Schuman-Olivier et al, 2014b). In terms of retention, published observational studies have generally reported six-month retention rates ranging from 25% (Matson et al, 2014) to 40 % (Schuman-Olivier et al, 2014a; Vo et al, 2016) and one-year retention rates between 9-17% (Smyth et al, 2012; Matson et al, 2014; Schuman-Olivier et al, 2014a; Mutlu et al.).…”
Section: Observational Studiesmentioning
confidence: 99%